IN VIVO TOXICITY PROFILE OF BRASSICA OLERACEA L. VAR.CAPITATA (CABBAGE) - KOMAL TALREJA,; ARCHANA MOON,; SURBHI SHIVHARE,; NINAD MOON,; AKSHAY DHOBLE,; SANJAY INGLE,; RADHIKA PAGEY, (International Journal of Pharma and Bio Sciences, 2015)
The cruciferae, Brassicaceae family, are characterized by the presence of a group of secondary metabolites called glucosinolates. More than 30 glucosinolates are present in the Brassica species. They are hydrolyzed by the enzyme myrosinase. Their breakdown products are chemically very reactive, and for a long time been known for their bioactive characteristics, such as anticarcinogenic, fungicidal or bactericidal properties. However, there is little information available about its toxicity profile. The present study was undertaken to investigate the potential toxic effects of methanolic extracts of Brassica oleracea L.var capitata (cabbage) in vivo. The toxic effects of extracts of Brassica oleracea were evaluated at different doses of hot soxhlet and cold macerated extracts. Alteration in SGOT, SGPT and ALP levels in a dose and concentration dependent manner was observed there by portraying its therapeutic and toxic concentrations.